SOLID STATE RELAY UNTUK AUTOMATIC TRANSFER SWITCH CCTV UNTUK PEMANTAUAN DI PERPUSTAKAAN - Diah Septi Yanaratri; Irianto; Putri Nur Cahyani; Renny Rakhmawati; Ahmad Firyal Adila; Sutedjo (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Monitoring in the library is very important. It is useful for reducing the high rate of crime, such as theft, that occurs today. However, CCTV systems can sometimes encounter issues, making a backup power source necessary to keep them operational. An Automatic Transfer Switch (ATS) is a device that automatically switches to a backup power source when a power outage occurs. When the main power supply from the utility company is restored, the power source switches back to the main supply and turns off the backup power source. In this ATS system, a Solid State Relay (SSR) is used to manage the switching process between the main and backup power sources. The backup power is provided by a battery connected to an inverter, with the battery being charged via a buck converter using the Constant Voltage (CV) method. Test results indicate that the ATS takes 42 milliseconds to switch from the main power source to the backup, causing a 50-second delay on the CCTV. On the other hand, switching back to the main power takes 10 milliseconds without any delay on the CCTV.